An accidental journalist [ the adventures of Edmund Stevens, 1934-1945 - Heckler, Cheryl , 1959- (Columbia : University of Missouri Press, 2007)
"Stevens was the longest-serving American-born correspondent working from within the Soviet Union. In his career, which spanned half a century, he distinguished himself as a war reporter, analyst, and cultural interpreter. Heckler focuses on Stevens's work, especially his reporting for the Christian Science Monitor, and his life from 1934 to 1945"--Provided by publisher
Description based on print version record
Includes bibliographical references (p 281-283) and index
Keywords: Stevens, Edmund; Journalist -- United States -- Biography